AUTONOMOUS MOBILE ROBOT DENGAN MENGGUNAKAN METODE SIMULTANEOUS LOCALIZATION AND MAPPING BERBASIS LIDAR - Mashur Arbi Maulana; Reynaldi Novian; Muhammad Iqbal Nugraha; I Made Andik Setiawan (Politeknik Manufaktur Negeri Bangka Belitung, 2022)
Autonomous mobile robot is a robot that can move independently from point to point. Which is important for working in dangerous area. To move independently, the robot must be able to identify its environment and know its position in the form of two-dimensional map. This research used Simultaneous Localization And Mapping (SLAM) method combined with of RPLidar A1M8 sensor and Robot Operating System(ROS) for identification the evironment. As a results, Autonomous robot is capable of mapping and delivering information of the robot can map and localize its position in an environment with mapping error 0,21% and 1,14% localization. Distance measurement in various angle tendts to stable with mean error 0,98%. Overall, the robot can be used in an empty area or an area with simple obstacle.